2016
DOI: 10.3390/ijerph13070678
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverage Consumption Is Adversely Associated with Childhood Attention Deficit/Hyperactivity Disorder

Abstract: Attention deficit/hyperactivity disorder (ADHD) is one of the most common childhood neurobehavioral conditions. Evidence of the negative effects of sugar-sweetened beverages (SSBs) on mental health has not been convincing, although a few studies have found an association between high SSB levels and attention problems in children. This study aimed to test the hypothesis that SSB consumption is associated with ADHD among children. Doctor-diagnosed ADHD cases (n = 173) and non-ADHD controls (n = 159) between age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 92 publications
6
28
0
4
Order By: Relevance
“…Other studies such as that of da Silva et al (23) and Muller et al (24) found no association. There was also no significant relationship between ADHD and the incidence of dopamine transporter allele in the study of Yu et al but a significant relationship was observed between this disease and the allele of dopamine receptor (25).…”
Section: Discussionmentioning
confidence: 55%
“…Other studies such as that of da Silva et al (23) and Muller et al (24) found no association. There was also no significant relationship between ADHD and the incidence of dopamine transporter allele in the study of Yu et al but a significant relationship was observed between this disease and the allele of dopamine receptor (25).…”
Section: Discussionmentioning
confidence: 55%
“…Some authors on the other hand have reported a greater correlation and believe there is a connection between ADHD and sugary drink consumption. [ 25 ]…”
Section: Effects On Healthmentioning
confidence: 99%
“…With the mass introduction of linoleic-acid-rich vegetable oils, such as that in Astrofood, the omega-6 to omega-3 ratio in the westernized diet is now around 16:1, and in some transitioning nations is as high as 50:1 [74]. Dominance of omega-6 relative to omega-3 has been linked to obesity, depression and childhood learning and behavioral disorders [75][76][77][78]; Second, added sugars, also foreign to ancestral experiences, have been linked with depression and behavioral disorders in human and animal research; mechanisms by which sugar could provoke mood, cognitive or behavioral disturbances include diminished levels of brain derived neurotrophic factor (BDNF) that otherwise supports stability and growth of nerves even past middle-age, elevation of inflammatory immune proteins such as cytokines (the elevation of which can compromise mood, disturb cognitive focus and increase anxiety), changes in blood-glucose-insulin control (which can effect subsequent mood), and addiction-like effects of sugar and sugar-fat combinations working through dopamine-mediated reward centers in the brain [79][80][81]. The effects of highly-palatable sugar or sugar-fat combinations may be especially disruptive to brain and behavior when encountered early in life [82].…”
Section: Deconstructing Astrofoodmentioning
confidence: 99%